The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/chem.200800095
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond Creates a Small Connecting Loop in Aminoxy Peptide Backbone

Abstract: Disulfide-bond formation between the side chains of cysteine-cysteine pairs is often critical to the folding behavior, stability, and functionality of proteins. In this paper, we report that sulfur atoms can be introduced into the amide groups of aminoxy peptides to form a novel type of disulfide bridge, which creates a connecting loop in the peptide backbone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…For example, α‐aminoxy peptides, analogues of β peptides in which the β carbon is replaced by an oxygen atom, adopt novel α NO turn structures involving eight‐membered‐ring intramolecular hydrogen bonds;7 β‐aminoxy peptides, analogues of γ peptides, can form nine‐membered‐ring intramolecular hydrogen bonds (β NO turns) and six‐membered‐ring bifurcated intramolecular hydrogen bonds;8 γ‐aminoxy peptides can induce γ NO turns involving ten‐membered‐ring intramolecular hydrogen bonds 9. We also found that a small connecting loop could be created by disulfide‐bridged dimers when the oxygen atom of an aminoxy amide group was substituted by a sulfur atom 10…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, α‐aminoxy peptides, analogues of β peptides in which the β carbon is replaced by an oxygen atom, adopt novel α NO turn structures involving eight‐membered‐ring intramolecular hydrogen bonds;7 β‐aminoxy peptides, analogues of γ peptides, can form nine‐membered‐ring intramolecular hydrogen bonds (β NO turns) and six‐membered‐ring bifurcated intramolecular hydrogen bonds;8 γ‐aminoxy peptides can induce γ NO turns involving ten‐membered‐ring intramolecular hydrogen bonds 9. We also found that a small connecting loop could be created by disulfide‐bridged dimers when the oxygen atom of an aminoxy amide group was substituted by a sulfur atom 10…”
Section: Introductionmentioning
confidence: 81%
“…[9] We also found that a small connecting loop could be created by disulfide-bridged dimers when the oxygen atom of an aminoxy amide group was substituted by a sulfur atom. [10] While oligomers consisting of consecutive a-, b-, or g-aminoxy acids can form helical structures (that is, N À O helices), reverse turns, sheets, and ribbon-like secondary structures, [7c-f, 8] the hybrid peptides containing alternating a-amino acids and a-aminoxy acids can induce 7/8 helices, and some peptides containing b-amino acids and a-aminoxy acids induce 12/10 helices. [11] Previously, the synthesis and conformational studies of several subclasses of b-aminoxy peptides, such as b 3 -, b 2, 2 -, Abstract: Herein, we report an efficient route for the asymmetric synthesis of b 2 -aminoxy acids as well as experimental and theoretical studies of conformations of peptides composed of b 2aminoxy acids.…”
Section: Introductionmentioning
confidence: 99%
“…26,44 Therefore, we focused on developing new single-source precursors for germanium and tin sulfide materials, and synthesized newly designed organic ligands containing sulfur atoms, such as mdpaSH, edpaSH, bdpaSH, and empaSH, using previously reported ligands. 52,53 Herein, we report the synthesis of new Ge and Sn complexes for use as chalcogenide materials and thin films as single-source precursors. Each molecule of the designed homoleptic compounds has one metal atom and two bidentate ligands containing two sulfur atoms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, we focused on developing new single-source precursors for germanium and tin sulfide materials, and synthesized newly designed organic ligands containing sulfur atoms, such as mdpaSH, edpaSH, bdpaSH, and empaSH, using previously reported ligands. , …”
Section: Introductionmentioning
confidence: 99%